The Use Of Augmented Reality (AR) And Virtual Reality (VR) In Modern Education - Ahmad Sa’adi (Journal of Education and Learning Sciences, 2024)
The integration of Augmented Reality (AR) and Virtual Reality (VR) in education has transformed traditional learning methods by offering immersive and interactive learning experiences. These technologies enable students to engage with digital content in ways that enhance understanding, retention, and engagement. This study explores the benefits, challenges, and future potential of AR and VR in modern education. Using a literature review approach, this study examines how AR and VR have been implemented in various educational fields, including STEM, medical training, and language learning. The findings highlight that AR and VR contribute to enhanced experiential learning, increased motivation, and better comprehension of complex concepts. However, challenges such as high costs, technical limitations, and the need for teacher training remain significant barriers to widespread adoption. This study suggests that affordable solutions, improved teacher preparedness, and better infrastructure are essential for maximizing the impact of AR and VR in education.